Parenting Fathers for Children during the Pandemic: Lessons Learned from Indonesia - Silvie Mil; Fasli Jalal; Martini Djamaris (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The COVID-19 pandemic has affected various aspects of life through social restrictions resulting in a shift in lifestyle. This study aims to explore the parenting practices of fathers in childcare during the pandemic. This study was conducted by distributing questionnaires and 111 fathers were asked about how they are financially responsible to their children, the interaction between father and son, and the affection given to the child during the pandemic. The results showed that fathers were positively involved with their children. More than 97% of fathers indicated their responsibility as the head of the family by providing finances to meet their children's basic needs (food, clothing, and housing) despite a decline in family income of 25-75% of pre-pandemic income. The involvement of fathers in parenting is not only shown by being actively involved in taking care of the children's basic needs, but also in planning for the children's future, developing children's talents, and helping activities related to school matters. Discipline children by enforcing family rules and boundaries about what children can and cannot do. The results also show that more than 60% of fathers often show their affection by hugging, touching, and kissing their children as well as giving praise for the right things their children do. The results of this study explain that fathers must still be involved in child care together with mothers even though the Covid-19 outbreak has been declared over.